2016
DOI: 10.1177/0081246316648517
|View full text |Cite
|
Sign up to set email alerts
|

The social construction of ‘deafness’: explored through the experiences of Black South African mothers raising a deaf child

Abstract: Individual realities and perceptions are embedded in a web of dominant social and cultural views which shape the individual. Mothers of deaf children therefore cannot be understood in isolation, and neither can their experiences, perceptions, and well-being. The present research investigated the construction of deafness through the experiences of mothers raising a deaf child and considered the manner in which these constructions impacted their well-being and relationship with the child. The study explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…One potential explanation might be related to the anticipated personal, medical, and social challenges associated with raising a deaf child by hearing potential parents (Plotkin et al, 2014), including the difficulties and medical challenges of choosing a cochlear implant, a hearing aid device (or none) (Haddad et al, 2019, Jackson & Turnbull, 2004. Nevertheless, the social construction of deafness (Kara & Harvey, 2017) might be another potential explanation for this specific result, potentially connected to the models of disability our participants generally adhere to, and future studies might benefit from further exploring it. In line with these results, another future research direction might explore the identity of the future child, as conceptualized by Solomon (2014).…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation might be related to the anticipated personal, medical, and social challenges associated with raising a deaf child by hearing potential parents (Plotkin et al, 2014), including the difficulties and medical challenges of choosing a cochlear implant, a hearing aid device (or none) (Haddad et al, 2019, Jackson & Turnbull, 2004. Nevertheless, the social construction of deafness (Kara & Harvey, 2017) might be another potential explanation for this specific result, potentially connected to the models of disability our participants generally adhere to, and future studies might benefit from further exploring it. In line with these results, another future research direction might explore the identity of the future child, as conceptualized by Solomon (2014).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that the well-being of mothers was negatively affected by negative social constructs of deafness (Kara & Harvey, 2017). Mothers were negatively affected by misconceptions related to deafness most notably through the pity they received from others.…”
Section: Societal Attitudes and Acceptancementioning
confidence: 98%
“…According to Kara and Harvey (2017), who conducted semi-structured interviews with South African mothers of children between three and eight years old, negative constructs of deafness lead to misconceptions that not only negatively affect mothers of children who are DHH but in turn negatively affect the children. This suggests a bi-directional relationship between parents of children who are DHH and their children, where that what negatively affects parents in turn affects their children.…”
Section: Societal Attitudes and Acceptancementioning
confidence: 99%
See 2 more Smart Citations